Plyometric jump training effects on the physicalfitness of individual-sport athletes: a systematic review with meta-analysis. - Sole, S.; Ramirez-Campillo, R.; Andrade, D. C.; Sanchez-Sanchez, J. (PeerJ, 2021)
Background: The aim of this study is to conduct a systematic review withmeta-analysis to explore the effects of plyometric jump training (PJT) on the physical fitness of individual sport athletes (ISA). Methods: Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, we searched through PubMed, Web of Science, andSCOPUS electronic databases. We included controlled studies that incorporated aPJT intervention among ISA (with no restriction for age or sex), that included apre-to-post intervention assessment of physical fitness (e.g., sprint; jump). From the included studies, relevant data (e.g., PJT and participants characteristics) was extracted. We assessed the methodological quality of the included studies using the PEDro scale. Using a random-effects model, meta-analyses for a given outcome was conducted. Means and standard deviations for a measure of pre-post-intervention physical fitness from the PJT and control groups were converted to Hedges`g effectsize (ES). Heterogeneity was assessed using the I2 statistic. The risk of bias was explored using the extended Egger`s test. The statistical significance threshold was set at p< 0.05. Moderator analyses were conducted according to the sex, age and sportbackground of the athletes. Results: Twenty-six studies of moderate-high methodological quality were included (total participants,n= 667). Compared to controls, PJT improved vertical jump (ES = 0.49;p< 0.001;I= 0.0%), linear sprint (ES = 0.23;p= 0.032;I2= 10.9%),maximal strength (ES = 0.50;p< 0.001;I2= 0.0%) and endurance performance (ES = 0.30;p= 0.028;I2= 11.1%). No significant effect was noted for sprint with change of direction (ES = 0.34;p= 0.205;I2= 70.9%). Athlete`s sex, age and sport background had no modulator role on the effect of PJT on vertical jump, linearsprint, maximal strength and endurance performance. Among the included studies, none reported adverse effects related to the PJT intervention. Conclusions: PJT induces small improvements on ISA physical fitness, including jumping, sprinting speed, strength and endurance.